2020
DOI: 10.1093/gji/ggaa253
|View full text |Cite
|
Sign up to set email alerts
|

Global adjoint tomography—model GLAD-M25

Abstract: SUMMARY Building on global adjoint tomography model GLAD-M15, we present transversely isotropic global model GLAD-M25, which is the result of 10 quasi-Newton tomographic iterations with an earthquake database consisting of 1480 events in the magnitude range 5.5 ≤ Mw ≤ 7.2, an almost sixfold increase over the first-generation model. We calculated fully 3-D synthetic seismograms with a shortest period of 17 s based on a GPU-accelerated spectral-element wave propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
174
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 69 publications
2
174
0
Order By: Relevance
“…In this section, we review results of previous seismological studies of the crust and upper mantle structure beneath Greenland and surrounding regions, focusing mainly on seismic tomography studies. The structure has been investigated using several tomographic methods with various spatial scales, including regionalscale surface wave tomography (Antonijevic & Lees, 2018;Darbyshire et al, 2004Darbyshire et al, , 2018Levshin et al, 2017;Mordret, 2018;Pourpoint et al, 2018), surface wave tomography of the North Atlantic region (Pilidou et al, 2004), body wave tomography of the whole Arctic region (Jakovlev et al, 2012), full waveform tomography of the North Atlantic region (Rickers et al, 2013), full waveform tomography of the whole Arctic region (Lebedev et al, 2017), and global tomography (e.g., Hosseini et al, 2020;Lei et al, 2020;Zhao, 2001Zhao, , 2004Zhao et al, 2013).…”
Section: Previous Studiesmentioning
confidence: 99%
“…In this section, we review results of previous seismological studies of the crust and upper mantle structure beneath Greenland and surrounding regions, focusing mainly on seismic tomography studies. The structure has been investigated using several tomographic methods with various spatial scales, including regionalscale surface wave tomography (Antonijevic & Lees, 2018;Darbyshire et al, 2004Darbyshire et al, , 2018Levshin et al, 2017;Mordret, 2018;Pourpoint et al, 2018), surface wave tomography of the North Atlantic region (Pilidou et al, 2004), body wave tomography of the whole Arctic region (Jakovlev et al, 2012), full waveform tomography of the North Atlantic region (Rickers et al, 2013), full waveform tomography of the whole Arctic region (Lebedev et al, 2017), and global tomography (e.g., Hosseini et al, 2020;Lei et al, 2020;Zhao, 2001Zhao, , 2004Zhao et al, 2013).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Considering these ambiguous results, Montelli et al (2006) suggested a possibility that the Iceland plume is not continuous but pulsating. More recent studies revealed further elusive features of this plume with a complicated shape not only in the vertical direction but also in the lateral direction (e.g., Zhao et al, 2013 and Hosseini et al, 2020 for global P wave tomography; Lei et al, 2020 for global S wave tomography; and Rickers et al, 2013 for regional S wave tomography). Zhao et al (2013) revealed a prominent localized low‐ V zone beneath Iceland down to ~500 km depth, whereas it becomes wider in the lower mantle (750–1,500 km depth) and less prominent in the lowermost mantle (2,300–2,800 km depth).…”
Section: Introductionmentioning
confidence: 98%
“…Attempts to reveal the shape and depth extent of the Iceland plume have been continued mainly by researchers of seismic tomography, which is a powerful tool used to obtain detailed 3-D images of underground structures. A consensus among these studies is the existence of an upper-mantle plume that extends down to at least 400 km depth, which is clearly revealed by both local/regional tomography (e.g., Allen et al, 2002;Foulger et al, 2000Foulger et al, , 2001Hung et al, 2004;Rickers et al, 2013;Wolfe et al, 1997) and global tomography (e.g., Hosseini et al, 2020;Lei et al, 2020;Zhao, 2001Zhao, , 2004Zhao et al, 2013). However, the existence of a lower-mantle plume beneath Iceland, as well as its depth extent, have long been hotly debated.…”
Section: Introductionmentioning
confidence: 99%
“…In principle this approach, which uses every wiggle on the seismograms, should be more powerful. But in practice it has important limitations (see Lei et al 2020). To produce global models with useful resolution requires the use of the most powerful computers that exist, and even then can only use a relatively small number of seismograms.…”
Section: Introductionmentioning
confidence: 99%
“…To produce global models with useful resolution requires the use of the most powerful computers that exist, and even then can only use a relatively small number of seismograms. Lei et al (2020) used 1480 earthquakes, or three orders of magnitude fewer than Priestley et al (2019) and Schaeffer and Lebedev (2013) used. Though the rapid improvement in computer power shows no sign of coming to an end, it is likely to continue to be overwhelmed by the continuing rapid increase in the number of digital seismometers generating seismograms.…”
Section: Introductionmentioning
confidence: 99%